Miejskie "luminalia" - w stronę krytycznej ontologii "elektropolis" - Sekuła, Elżbieta Anna (Er(r)go. Teoria - Literatura - Kultura, 2006)
Elżbieta Anna Sekuła, Urban Luminalia. Towards a Critical Ontology of Electropolis The article provides a critical examination of the contemporary city, characterised here as post-polis in the context of contemporary cultural and media theory.